2002
DOI: 10.1016/s0960-9822(02)00839-4
|View full text |Cite
|
Sign up to set email alerts
|

Robustness, Flexibility, and the Role of Lateral Inhibition in the Neurogenic Network

Abstract: The neurogenic network is robust to changes in parameter values, which gives it the flexibility to make new patterns. Our model also offers a possible resolution of a debate on the role of lateral inhibition in cell fate specification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
110
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(111 citation statements)
references
References 21 publications
1
110
0
Order By: Relevance
“…Analysis and numerical simulation demonstrates another surprising result: even with lateral inhibition in ligand production, patterns of wavelength longer than two or three cells are predicted. It has been suggested recently that lateral inhibition must be combined with other mechanisms to give longer wavelength patterns, such as cell growth [4], long-range filapodial contacts [24], or paracrine signalling [17,33]. However, we have shown that lateral inhibition can be sufficient by itself to predict longer-range patterns without the need for additional long range effects.…”
Section: Discussionmentioning
confidence: 55%
“…Analysis and numerical simulation demonstrates another surprising result: even with lateral inhibition in ligand production, patterns of wavelength longer than two or three cells are predicted. It has been suggested recently that lateral inhibition must be combined with other mechanisms to give longer wavelength patterns, such as cell growth [4], long-range filapodial contacts [24], or paracrine signalling [17,33]. However, we have shown that lateral inhibition can be sufficient by itself to predict longer-range patterns without the need for additional long range effects.…”
Section: Discussionmentioning
confidence: 55%
“…By necessity, their analysis often focuses on one or a few functions, and robustness of this function does not necessarily mean robustness of other functions. However, the robustness of one function may allow the network to acquire other functions (14,58). Finally, and most importantly, which quantitative oscillator model is the correct one?…”
Section: Discussionmentioning
confidence: 99%
“…Such models help understand processes as different as bacterial chemotaxis (1), circadian rhythms (2-10), organismal development (11)(12)(13)(14)(15), and the behavior of synthetic circuitry (16)(17)(18)(19). Most such models represent biological circuits through differential equations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Do cells need genes that function mainly as canalizing agents? Many studies (von Dassow et al 2000;Meir et al 2002;Siegal and Bergman 2002) suggested that complex networks, such as cellular transcription networks, are inherently stable. von Dassow et al (2000) analyzed the segment polarity phenotype, attempting to simulate the 14-stripe pattern in Drosophila development.…”
Section: Do Canalizing Genes Exist?mentioning
confidence: 99%